Analisis Penerapan Metode Inkuiri Terbimbing Pada Mata Pelajaran Akuntansi Melalui Studi Kepustakaan - Suci Auliah Ramadhani; Abel Safitri Aulia; Zahrah Abel Febilia; Sri Ayu Pratiwi; Umayyah M.; Nur Fadila Saenal (PT. Citra Media Publishing, 2025)
This study aims to analyze the implementation of guided inquiry methods in accounting education and their impact on students' analytical abilities through library research. A qualitative research was conducted by examining relevant literature, including books, articles, and journals. The analysis technique employed literature study by identifying, collecting, and analyzing library sources related to guided inquiry methods. Research findings indicate that guided inquiry methods provide significant contributions in improving learning outcomes, student interest, and analytical thinking skills in accounting subjects. This method encourages active student participation in the learning process with teacher guidance, developing positive character traits including fairness, honesty, discipline, creativity, independence, responsibility, and tolerance. The research concludes that the guided inquiry approach is effective in enhancing the quality of accounting education and comprehensive student potential development.